2017
DOI: 10.2519/jospt.2017.7389
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inclusion of Dry Needling in a Multimodal Therapy Program for Patellofemoral Pain: A Randomized Parallel-Group Trial

Abstract: Study Design Randomized controlled trial. Background Evidence suggests that multimodal interventions that include exercise therapy may be effective for patellofemoral pain (PFP); however, no study has investigated the effects of trigger point (TrP) dry needling (DN) in people with PFP. Objectives To compare the effects of adding TrP DN to a manual therapy and exercise program on pain, function, and disability in individuals with PFP. Methods Individuals with PFP (n = 60) recruited from a public hospital in Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…A new high-quality RCT evaluating dry needling to trigger points27 was identified in the 2017 update. While the expert panel acknowledged that acupuncture and trigger point dry needling have key differences in their clinical indication and application, it was decided to group them in a single recommendation on the basis that evidence for both was limited and uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A new high-quality RCT evaluating dry needling to trigger points27 was identified in the 2017 update. While the expert panel acknowledged that acupuncture and trigger point dry needling have key differences in their clinical indication and application, it was decided to group them in a single recommendation on the basis that evidence for both was limited and uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Deep dry needling (DDN) is a minimally invasive therapy frequently included in the treatment of multiple pain conditions. Previous research has investigated its effectiveness in patients presenting with disorders such as nonspecific low back [1], neck, or shoulder pain [2]; lateral epicondylalgia [3]; temporomandibular disorders [4]; plantar heel pain [5]; or patellofemoral pain [6]. A recent meta‐analysis has concluded that very low‐to‐moderate evidence supports its effectiveness against no treatment or placebo improving pain in the short and medium term [7].…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were history of fracture, dislocation, or surgery in the lower extremity or trunk regions; any self‐reported history and clinical evidence of recent ligament sprain, meniscal defect, chondral lesion, or disease of the patellar tendon; osteoarthritis; history or clinical evidence of low back pain or sacroiliac joint dysfunction during the previous 6 months; disk herniation or referred spinal pain; any other disorders such as neurologic disorders that might interfere with the kinematics or kinetics of trunk, hip, knee and ankle motion; and participation in professional athletic activities. In addition, any systemic disease that could affect our results, for example, cardiovascular, metabolic or respiratory disease, pregnancy, or breastfeeding (current or within the preceding year), implantable or injectable contraceptive use, and premenstrual syndrome (Appendix 3) were considered exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%